Evaluation of soybean genotype tolerance to water stress during germination (Bioagro, 2025)
Water deficit is a major limiting factor for crop productivity and significantly impacts the viability and vigor of soybean seeds (Glycine max). This study aimed to evaluate the effects of water deficit on the germination-emergence phenological stage in soybean genotypes classified as either drought-tolerant or sensitive during flowering. The experiment followed a completely randomized design with four replications. A factorial scheme of 10 × 6 was used, comprising 10 soybean genotypes (genotype 1, genotype 2, genotype 3, genotype 4, genotype 5, genotype 6, genotype 7, genotype 8, genotype 9, and genotype 10) and six osmotic potentials (-0.0, -0.2, -0.4, -0.6, -0.8, and -1.0 MPa), achieved using polyethylene glycol 6000 (PEG 6000). The analyzed variables included first germination count and germination percentage (from the germination test), shoot and root length, shoot and root dry mass (from the seedling growth test), and vigor from the cold test. Data were fitted to regression models. The results showed that reducing the osmotic potential with PEG 6000, from -0.2 MPa onwards, negatively affected the germination and vigor of soybean seeds, regardless of whether the genotypes were drought-tolerant or sensitive during flowering. Soybean genotypes displayed varying responses to water deficit during the germination-emergence stage, indicating that drought tolerance during flowering does not necessarily predict their performance under water stress at earlier growth stages.
Keywords: Drought stress; Glycine max; physiological quality of seeds; polyethylene glycol; viability